Collaboration Across Boundaries for Social-Ecological Systems Science Experiences Around the World - Perz, Stephen G. (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
"This is a book that any researcher contemplating a large scale interdisciplinary research project investigating social-ecological systems should read. It provides real world tangible examples of such projects and offers lessons that can be used by others to be more successful in their own research efforts." - Robert J Summers, Academic Director, Sustainability Council, University of Alberta, Canada Collaboration across boundaries is widely recognized as a vital requisite for the advancement of innovative science to address problems such as environmental degradation and global change. This book takes collaboration across boundaries seriously by focusing on the many challenges and practices involved in team science when spanning disciplinary, organizational, national and other divides. The authors draw on a shared framework for managing the challenges of collaboration across boundaries as applied to the science of understanding complex social-ecological systems. Teams working across boundaries on diverse social-ecological systems in countries around the world report their challenges and share their practices, outcomes and lessons learned. From these diverse experiences arise many commonalities and also some important differences. These provide the basis for a set of recommendations to any collaborators intending to use science as a tool to better understand social-ecological systems and to improve their management and governance. Stephen G. Perz is Professor in the Department of Sociology and Criminology & Law at the University of Florida, USA. He works collaboratively on conservation and development issues in the Amazon, crossing disciplinary, organizational and national boundaries. This work has been funded by NASA, NSF, USAID, the Moore Foundation, and other sources, and has resulted in over 100 publications in peer-reviewed scholarly outlets.